I am not sure my clarification to my question came through, so I am posting it again.

**White Noise, let me clarify** = 3/n [ 7 + 6/n = 7 + 12/n + ....+ 7 + 6n/n] goes to
= 3/n [ ( 7 + 7 + 7) + (6/n + 12/n + ....+ 6n/n)] which goes to

= 3/n[ 7n + 6/n (1 + 2 +...+n)] which goes to

= 3/n[ 7n + 6/n * n(n+1)/2 ]

= 3/n [7n + 3((n+1)]

= 3/n[ 7n + 3n + 3]

= 3/n [10n + 3]

= 30 + 9/n I do not understand the algebra. I do not see how the term 6n/n was factored out and became 7n + 6/n(1+2+....+n) Can you please explain the algebra that accomplishes this? Thanks